72 A microencapsulated blend of essential oils and dead yeast culture on the performance of nellore bulls finished in feedlot. (7th December 2018) - Martins, L; Fernandes, J; Drouillard, J; Leite, L; Araujo, R
Abstract: A finishing feedlot study was conducted at the Centro de Pesquisa Nutripura (Mato Grosso State, Brazil) to examine the effects of a microencapsulated blend of essential oils (EO; Activo Premium ® ) and dead yeast culture (YC; Factor SC ® ) fed alone or combined with monensin (MON) on growth of feedlot bulls. A total of 930 bulls were blocked by initial BW (450 ± 48 kg) and randomly assigned to 30 pens (experimental unit). Treatments fed for 91 d were: MON, 30 mg/kg DM; EO, 150 mg/kg DM; YC, 700 mg/kg DM; MON+EO, 30 + 150 mg/kg DM; MON+YC, 30 + 700 mg/kg DM. Animals were stepwise adapted for 21 d to achieve a final diet fed for additional 70 d and composed of 14% grass silage, 54% ground corn, 21% soyhulls, 7.5% soybean meal, and 3.5% mineral-vitamin premix (DM basis). Animals fed MON+EO had a greater ADG than MON (1.788 vs. 1.719 kg; P = 0.02) and tended to show a greater final BW (614 vs. 606 kg; P = 0.06). The YC had a lower ADG than MON (1.641 vs. 1719 kg; P = 0.02). The EO and YC increased DMI when contrasted with MON (12.18 vs. 11.85 vs. 11.48 kg/d; P < 0.01), with MON+EO and MON+YC not differing from MON ( P > 0.15). The MON had a greater feed efficiency when contrasted with EO or YC (0.150 vs. 0.141 vs. 0.138; P < 0.01), whereas MON+EO tended to present greater feed efficiency than MON (0.154 vs. 0.150; P = 0.09). The MON resulted in a lower incidence of laminitis than EO or YC ( P < 0.03), with MON+EO and MON+YC not differing ( P > 0.21) from MON. In conclusion, the use of essential oils combined with monensin improved the performance of feedlot bulls when compared with monensin alone.